Action Monitoring in Children with or without a Family History of ADHD – Effects of Gender on an Endophenotype Parameter - Albrecht, Björn (2009)
Attention-deficit/hyperactivity disorder (ADHD) is a frequent and highly heritable disorder overrepresented in boys. In a recent study investigating boys only, we found that action monitoring deficits as reflected by certain behavioral and electrophysiological parameters were familially driven. As gender may also have an important impact, this was examined in the current study with nonaffected children aged 8 to 15 years having relatives suffering from ADHD (N=37, 21 ♀) and with age-matched controls without family history of ADHD (N=33, 11 ♀). Extending our previous findings that action monitoring is a potential endophenotype for boys with ADHD, familially driven deficits were confirmed independently of gender. Thus, despite sharing the phenotype with controls, nonaffected siblings showed ADHD-like impairments albeit of smaller magnitude. However, girls performed generally more accurately, which in turn may have produced the differences between nonaffected siblings and controls in affective error processing that were not present in our boys-only assessment.